2023
DOI: 10.1097/gh9.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

How gender disparities affect otolaryngology specialty selection: an international cross-sectional survey

Abstract: Introduction: Most studies evaluating gender disparities in surgical specialties as a career choice are limited to high-income countries and have largely evaluated surgical subspecialties in aggregate. Objective: This study aimed to describe gender-based differences in otolaryngology specialty selection amongst medical students, trainees, and attendings/consultants across both low- and middle-income (LMICs) and high-income countries. Materials and methods: An online cross-sectional survey with 2 arms was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In another study conducted by among medical students from both HICs and LMICs, >50% of respondents were interested in pursuing OHNS as a career, but females were twice as unlikely to be interested in OHNS compared to male students [1 ▪▪ ].…”
Section: Recent Findingsmentioning
confidence: 93%
See 4 more Smart Citations
“…In another study conducted by among medical students from both HICs and LMICs, >50% of respondents were interested in pursuing OHNS as a career, but females were twice as unlikely to be interested in OHNS compared to male students [1 ▪▪ ].…”
Section: Recent Findingsmentioning
confidence: 93%
“…Nuss et al [1 ▪▪ ] reported that while a majority of male residents and attendings believed OHNS training is equally welcome to all genders, female attendings and residents did not believe this to be true. This further reinforces the unseen impact of gender disparities, especially when they are not discussed and actively dealt with.…”
Section: Recent Findingsmentioning
confidence: 99%
See 3 more Smart Citations